Produção de textos narrativos no 6º ano do Ensino Fundamental: um estudo sobre propostas em livros didáticos do PNLD de 2020 - Monteiro, Danilo Silva (2023)
This dissertation is in the line of research "Reading, Writing and Teaching on the Portuguese Language" of the Post-Graduate of the Portuguese Language Program from the Pontifical Catholic University of São Paulo, and its theme is of the analysis of the proposal of narrative texts production on didactic books of the Portuguese Language, approved by the National Book and Didactic Coursework Program of 2022. The research questions that guide this study are: How are the proposed activities for the production of narrative texts organised in the Portuguese language textbooks for Year 6 of Elementary School in the 2020 PNLD? How do the proposals for the production of narrative texts in textbooks contemplate the skills provided for in the BNCC, specially with regards to creativity? To answer those questions, the general objective is: to verify how the activities for teaching narrative texts in textbooks for students of Year 6 of Elementary School- Final years are oriented, and if they are organised by narrative textual sequences. The specific objectives are: 1) Identify, describe and analyse the proposed activities for the production of narrative texts in textbooks of Year 6 of Elementary School- Final years; 2) Comparatively discuss the results of the analysis and relate them to what the BNCC proposes as the treatment of the production of narrative texts, with regards to the development of creativity. To achieve these objectives, this study will be based on theoretical: Cavalcante et al. (2010), Fávero and Koch (2012 [1983]), Koch (2019; 2018), Marcuschi (2012, 2008) and Marquesi (2004), with regards to the principles of Textual Linguistics and b) Adam (2019, 2017, 2011), Marquesi (2017), Marquesi, Cabral and Silveira (2016), Oliveira (2016), Marquesi, Pauliukonis and Elias (2017), Passeggi et al. (2010), with regards to the principles of Textual Analysis of Discourses. The main body is composed of six didactic proposals of narrative text Production, each one selected from one of the approved books from the PNLD 2020. The results allow us to confirm that the didactic proposals of the narrative text Production, if organised by the narrative text sequences, may develop the understanding of students to the process of narrative production